MENGANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA TERPELESET, TERSANDUNG, DAN JATUH DENGAN PENERAPAN METODE PENAMBANGAN DATA KE BASIS DATA STATISTIK KECELAKAAN DAN PENYAKIT AKIBAT KERJA DI PERTAMBANGAN - Aghnina Fazura; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Mining is known as a high risk industry with a high accident rate. However, there is a dearth of materials that aim to hide and understand mining accident research trends and current scenarios related to this topic. Therefore, this systematic assessment aims to investigate research trends in mining accidents. By applying the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method, a systematic literature assessment (SLR) identified 57 cases related to mining accident issues from 2015 to 2019 from the ScienceDirect and Scopus databases. Based on these 57 studies, four main themes were raised, namely the main causes of mining accidents (46%), prevention of mining accidents (20%), and lawsuits (17%) and the impact of post- mining accidents (17%). The four themes produce a total of 35 sub-themes. Engineering failures are identified as a major cause of mining accidents and the application of safety software or models is essential to minimize the number of mining accidents. Mine owners have a responsibility to provide a safe working environment for their miners, and there are major challenges to achieving this. In addition, the impact of post-mining accidents has a negative impact on the environment. This systematic appraisal study aims to assist mine owners by providing a better understanding of the problem of mining accidents. This study is also addressed to miners, government, and policy makers so that all parties can jointly target mining accidents in the future